The state and consideration for skin test of β-lactam antibiotics in pediatrics - Gao, Chunhui; Ma, Bowen; Liu, Wei; Zhu, Liqin (Frontiers in Cellular and Infection Microbiology, 2023)
β-lactam antibiotics are the most frequently used drugs and the most common drugs that cause allergic reactions in pediatrics. The occurrence of some allergic reactions can be predicted by skin testing, especially severe adverse reactions such as anaphylactic shock. Thus, penicillin and cephalosporin skin tests are widely used to predict allergic reactions before medication in pediatrics. However, false-positive results from skin tests were more often encountered in pediatrics than in adults. In fact, many children labeled as allergic to β-lactam are not allergic to the antibiotic, leading to the use of alternative antibiotics, which are less effective and more toxic, and the increase of antibiotic resistance. There has been controversy over whether β-lactam antibiotics should be tested for skin allergies before application in children. Based on the great controversy in the implementation of β-lactam antibiotic skin tests, especially the controversial cephalosporin skin tests in pediatrics, the mechanism and reasons of anaphylaxis to β-lactam antibiotics, the significance of β-lactam antibiotic skin tests, the current state of β-lactam antibiotic skin tests at home and abroad, and the problems of domestic and international skin tests were analyzed to determine a unified standard of β-lactam antibiotic skin tests in pediatrics to prevent and decrease adverse drug reactions, avoid waste of drugs, and a large amount of manpower and material resource consumption.